Hiking physiology and the "quasi-isometric" concept - Spurway, N. C. (Journal of Sports Sciences, 2007)
The literature indicates that the heart rate of a planing-dinghy sailor, in winds of 4 - 5 m · s-1, is in the range seen in aerobic athletes, yet oxygen consumption (O2) is roughly half that of the same individual cycling at that heart rate. Thus, although upper-body dynamic activity is a contributing factor, the dominant physiological demand must be the "quasi-isometric" stress on the lower-body anterior muscles - especially the quadriceps, which appears to impose 40 - 50% of the total oxygen demand in a typical hiking posture. Therefore, a non-trivial part of the sailor's fitness training should involve sustained quadriceps stress.